SELF-DEVELOPMENT - YOUTH OF THE XXI CENTURY MAIN TASK - Zhiyenbayeva Bogdagul (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the specific aspects of self-development among the youth of the 21st century in the context of a rapidly changing world. It examines the key factors influencing personal and professional growth, including digital transformation, the rise of soft skills, educational trends, and the role of social media. Special attention is given to issues of motivation, self-identification, and critical thinking in the age of information overload. The author emphasizes the importance of a conscious approach to self-development as a foundation for the successful integration of young people into modern society.